2019
DOI: 10.1177/1073274819864641
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Among Inpatients With Cancer: Findings From a Hospital-Based Cross-Sectional Study in Vietnam

Abstract: Anxiety, a condition which is commonly found in patients with cancer, has negative impacts on their quality of life and treatment outcome. This study aimed to determine the level of anxiety in patients with cancer and explore sociodemographic, disease-related, and hospital-related factors associated with anxiety in those patients. A cross-sectional study was conducted on 510 inpatients with cancer at Thanh Hoa Oncology Hospital, Vietnam. Data were collected from self-administered questionnaire forms on hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
4
17
1
Order By: Relevance
“…Our results also identified that married workers with cancer have less symptoms of anxiety. This finding is similar with recent study conducted in Vietnam that evaluated anxiety among patients with cancer through a hospital based cross-sectional study [27]. Reason for this is because generally, married patients with cancer perceive more social support than unmarried or separated individuals.…”
Section: Resultssupporting
confidence: 91%
“…Our results also identified that married workers with cancer have less symptoms of anxiety. This finding is similar with recent study conducted in Vietnam that evaluated anxiety among patients with cancer through a hospital based cross-sectional study [27]. Reason for this is because generally, married patients with cancer perceive more social support than unmarried or separated individuals.…”
Section: Resultssupporting
confidence: 91%
“…Such precautionary measures would have been a major inconvenience for patients in the pre-COVID era by creating longer queues and discomfort. Anxiety is a common problem in cancer patients and will negatively impact their quality of life, treatment satisfaction, and outcome [17]. The fear of contracting coronavirus aggravates this problem, as shown in our study that 81% of the patients were afraid of being infected while undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 68%
“…We considered a score of 8-10 to represent borderline abnormality and 11-21 to represent symptoms of anxiety or depression (25). In this study, we referred to the Vietnamese translation version of the HADS, whose validity and reliability were con rmed in the previous studies with Cronbach's alpha as 0.80 for the HADS-D and 0.85 for the HADS-A (26,27).…”
Section: Vietnamese Translation Scales For Qol and Health Statusmentioning
confidence: 99%